KEPUASAN MAHASISWA UBJJ-UT BANDUNG TERHADAP MANAJEMEN PENGELOLAAN BIMBINGAN AKADEMIK PRAKTIKUM SELAMA PANDEMI TAHUN 2021 - Maman Sudirman; Angga Sucitra Hendrayana; Dina Thaib (Universitas Islam Negeri Alauddin Makassar, 2022)
This study aims to analyze the management of academic counseling for students who participated in laboratory work. Five functions of academic counseling management were analyzed: organizing, planning, controlling, communicating, and directing. The method used in this research is descriptive quantitative. The sample in this study was 32 students who participated in the 2021 laboratories working at UPBJJ-UT Bandung. The instrument used is a questionnaire in the form of a Likert scale. From the data processed, all the average values ​​of the 20 statement items are close to the maximum value (5). It can conclude that the laboratory work management at UPBJJ-UT Bandung is adequate and going as expected. The students' opinions regarding completeness can still be considered feasible during laboratory work activities.